Public Policies: An analysis from the evidence-based approach in Social Work - Díaz-Valdés, Antonia (Critical Proposals in Social Work, 2023)
One of the answers to the ethic reference in Social Work is the Evidence Based Approach. However, its use it is not limited to Social Work, in fact this approach supports a large proportion of decision made at the policy level today. Through, the public policies the State seeks the wellbeing of the population. Thus, it is important to show evidence about the implementation of such policies and how those meet their aims. At this point the proposed Evidence-Based Public Policy gains importance as a contemporary theoretical approach for Social Work, through its theoretical-critically analysis. The discourses and voices presented in this study are based on analysis of semi-structured interviews with social work professionals who have worked or are working with the approach.